2021
DOI: 10.21203/rs.3.rs-910016/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

YY1 lactylation in microglia promotes angiogenesis through transcription activation-mediated upregulation of FGF2

Abstract: Ocular neovascularization is a leading cause of blindness. Retinal microglia have been implicated in hypoxia-induced angiogenesis and vasculopathy, but the underlying mechanisms remain largely unknown. Here, we report that lactylation in microglia is critical for retinal neovascularization. Using lactylome and proteomic analyses, we identified a list of hyperlactylated proteins in the context of increased lactate under hypoxia. Yin Yang-1 (YY1), a transcription factor, is lactylated at lysine 183 (K183) under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…YY1 is directly bound to the promoter of FGF2 and promotes the transcription of FGF2 through its high lactylation, thus promoting the formation of neovascularization. This situation is reversed by the p300/CBP inhibitor A-485 [110].…”
Section: Other Epigenetic Regulationsmentioning
confidence: 96%
See 2 more Smart Citations
“…YY1 is directly bound to the promoter of FGF2 and promotes the transcription of FGF2 through its high lactylation, thus promoting the formation of neovascularization. This situation is reversed by the p300/CBP inhibitor A-485 [110].…”
Section: Other Epigenetic Regulationsmentioning
confidence: 96%
“…In addition to those above, lactate-induced lactylation can additionally contribute to DNA repair, embryo implantation, and the improvement of the fatty liver, but it can also lead to the worsening of pulmonary hypertension and proliferative retinopathies [105][106][107][108][109][110]. Sun Y et al [105] found that hyperlactylation of PARP1 regulated its ADP-ribosylation activity and might contribute to DNA repair based on an alkynyl-functionalized bioorthogonal chemical reporter, YnLac.…”
Section: Other Epigenetic Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, studying the correlation between lactylation and other modifications linked to heart disease and its regulatory mechanism would enhance understanding of the etiology of the disease. Finally, investigating the involvement of lactylation in various tissues and diseases can enhance our comprehension and potential utilisation of this process (7,8).…”
Section: To the Editormentioning
confidence: 99%
“…The raw and processed proteomic and lactylome data are available in the Proteomics Identification Database with accession number PXD028737 [62]. All microscopy images are available at Figshare repositor [63]. All the other data generated in this study are included in the article and the Additional files.…”
Section: Supplementary Informationmentioning
confidence: 99%